High TLR7 Expression Drives the Expansion of CD19+CD24hiCD38hi Transitional B Cells and Autoantibody Production in SLE Patients - Wang, Ting; Marken, John; Chen, Janice; Tran, Van Bao; Li, Quan-Zhen; Li, Mengtao; Cerosaletti, Karen; Elkon, Keith B.; Zeng, Xiaofeng; Giltiay, Natalia V. (Frontiers in Immunology, 2019)
Signaling through Toll-like receptor 7 (TLR7) drives the production of type I IFN and promotes the activation of autoreactive B cells and is implicated in the pathogenesis of systemic lupus erythematosus (SLE). While TLR7 has been extensively studied in murine lupus, much less is known about its role in the pathogenesis of human SLE. Genetic studies support a link between the TLR7 rs3853839 C/G polymorphism, which affects TLR7 mRNA turnover, and SLE susceptibility; however, the effects of this polymorphism on B cells have not been studied. Here we determined how changes in TLR7 expression affect peripheral B cells and auto-Ab production in SLE patients. High TLR7 expression in SLE patients driven by TLR7 rs3853839 C/G polymorphism was associated with more active disease and upregulation of IFN-responsive genes. TLR7hi SLE patients showed an increase in peripheral B cells. Most notably, the percentage and numbers of CD19+CD24++CD38++ newly-formed transitional (TR) B cells were increased in TLR7hi SLE patients as compared to HCs and TLR7norm/lo SLE patients. Using auto-Ab arrays, we found an increase and enrichment of auto-Ab specificities in the TLR7hi SLE group, including the production of anti-RNA/RNP-Abs. Upon in vitro TLR7 ligand stimulation, TR B cells isolated from TLR7hi but not TLR7norm/lo SLE patients produced anti-nuclear auto-Abs (ANA). Exposure of TR B cells isolated from cord blood to IFN induced the expression of TLR7 and enabled their activation in response to TLR7 ligation in vitro. Our study shows that overexpression of TLR7 in SLE patients drives the expansion of TR B cells. High TLR7 signaling in TR B cells promotes auto-Ab production, supporting a possible pathogenic role of TR B cells in human SLE.